The cause, interpretive effects, and scribal motivations of alternative literary sequences in G and M proverbs - Justiss, J (2024)
This dissertation examines the variant sequences of large text-blocks to which the ancient Greek version of Proverbs (G Proverbs) witnesses vis-à-vis the sequence of the same material to which the Masoretic version of Proverbs (M Proverbs) witnesses. This order difference concerns the variant location in G of Prov 30:1-14 (inserted following Prov 24:22 in G’s sequence) and 30:15-31:9 (inserted after Prov 24:34 in G’s sequence). This arrangement also creates the variant sequence of Prov 29 to Prov 31:10-31. I focus on the Prov 24:22 to 30:1 sequence and the Prov 29:27 to 31:10 sequence to answer the question whether G’s translator or G’s source is the cause of the variant orders.